Brain lesions and cognitive decline in patients with atrial fibrillation: a prospective multicentre cohort study (Swiss Medical Weekly, 2026)
STUDY AIM: Atrial fibrillation (AF) is associated with a high burden of vascular brain lesions, most of which are covert. We aimed to assess the association between vascular brain lesions (brain infarcts, microbleeds, white matter lesions) and cognitive decline over time in atrial fibrillation patients.METHODS: We included 1536 atrial fibrillation patients with brain magnetic resonance imaging (MRI) from a prospective multicentre cohort study. Patients were enrolled between 2014 and 2017 across 14 centres in Switzerland. Their cognitive functioning was assessed at baseline and yearly intervals using Montreal Cognitive Assessment (MoCA) and Cognitive Construct (CoCo) scores. Cognitive decline was defined as a score decline of >1 standard deviation of the age- and education-standardised baseline population compared with individual baseline levels of the corresponding test.RESULTS: Of 1536 patients, 1030 (mean age: 72 years; 73% male) had ≥1 vascular brain lesion on baseline MRI. During a median follow-up of 5.13 years, cognitive decline developed in 159 (10%) patients based on MoCA scores and in 144 (9%) based on CoCo scores. The incidence rate (per 100 person-years) for cognitive decline was 3.64 in patients with brain lesions vs 1.82 in patients without brain lesions on baseline MRI using MoCA scores, and 3.18 vs 2.0 using CoCo scores. In multivariable adjusted Cox proportional hazard models, the hazard ratio (HR) (95% confidence interval [CI]) of any brain lesion for cognitive decline was 1.29 (0.85–1.96) using the MoCA and 1.45 (0.95–2.20) using the CoCo score.CONCLUSIONS: In our atrial fibrillation cohort, the presence of brain lesions was not associated with a higher risk of cognitive decline using the MoCA or the CoCo score. However, there was an association with more-specific cognitive domains.Trial registration: https://clinicaltrials.gov NCT02105844.